Systematic review and meta‐analysis of the effect of the World Health Organization surgical safety checklist on postoperative complications. Issue 3 (February 2014) - Bergs, J.; Hellings, J.; Cleemput, I.; Zurel, Ö.; De Troyer, V.; Van Hiel, M.; Demeere, J.‐L.; Claeys, D.; Vandijck, D.
<x xml:space="preserve">Abstract</x> Background The World Health Organization (WHO) surgical safety checklist (SSC) was introduced to improve the safety of surgical procedures. This systematic review evaluated current evidence regarding the effectiveness of this checklist in reducing postoperative complications. Methods The Cochrane Library, MEDLINE, Embase and CINAHL were searched using predefined inclusion criteria. The systematic review included all original articles reporting a quantitative measure of the effect of the WHO SSC on postoperative complications. Data were extracted for postoperative complications reported in at least two studies. A meta‐analysis was conducted to quantify the effect of the WHO SSC on any complication, surgical‐site infection (SSI) and mortality. Yule's Q contingency coefficient was used as a measure of the association between effectiveness and adherence with the checklist. Results Seven of 723 studies identified met the inclusion criteria. There was marked methodological heterogeneity among studies. The impact on six clinical outcomes was reported in at least two studies. A meta‐analysis was performed for three main outcomes (any complication, mortality and SSI). Risk ratios for any complication, mortality and SSI were 0·59 (95 per cent confidence interval 0·47 to 0·74), 0·77 (0·60 to 0·98) and 0·57 (0·41 to 0·79) respectively. There was a strong correlation between a significant decrease in postoperative complications and adherence to aspects of care embedded in the checklist (Q = 0·82; P = 0·042). Conclusion The evidence is highly suggestive of a reduction in postoperative complications and mortality following implementation of the WHO SSC, but cannot be regarded as definitive in the absence of higher‐quality studies.